Optimization Design of Multifunction Machines For Making 2 Kinds of Animal Feed - Riki Effendi; Fadwah Maghfurah; Rudiarto Rudiarto (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2018)
Optimization design of multifunctional machines for making of animal feed is one of the development efforts of conventional machinery to be a multifunctional machine with electric motor drive which is to help small MSME industries so that their results and capacity are faster and more effective during the process of milling and grinding. This is a new concept designed to increase the time effectiveness of its use. This tool is specifically designed to chop odot grass and grind corn kernels, where the tool works using resources from an electric motor that moves a U-type blade or type I blade for knitting or grinding. The method used to make multifunction machines includes the development of existing models, seeking research on previous tools, refining the design model concept, making 3D models using the Solidworks Computer Aided Design (CAD) with a cycle time of 50 seconds on different test pieces and mills where assembly time is needed to complete the multifunction machine for ± 20 days or 28800 minutes.